Legal Barriers And Women’s Rights In Muslim Marriages: Shariah Lawyers' Thoughts On Emotional Abuse In Terengganu - Nurul Farhana Azmi; Kauthar Razali; Norazilawati Abd Wahab; Nurshuhada Mohamed; Wan Nur Izzati Wan Nor Anas; Abdul Mufid (Universiti Sains Islam Malaysia, 2026)
Increasing mental health concerns in Malaysia have intensified the focus on emotional harm within marriage, specifically cumulative and private abuse that lacks physical evidence. This study investigates the legal and procedural barriers faced by women seeking fasakh (divorce) on grounds of emotional abuse within the Shariah court system of Terengganu. Despite Terengganu recording the highest score in the Malaysia Happiness Index 2024 (8.64), psychological harms remain a hidden challenge. Adopting a mixed-method design, the research analyzed a cross-sectional survey of 31 Shariah lawyers via SPSS and performed a structured content analysis of 33 fasakh case documents. The findings reveal three critical challenges to women's rights: (1) evidentiary limitations and social stigma that complicate the burden of proof; (2) legal ambiguity in the framing of emotional abuse leading to inconsistent judicial outcomes; and (3) a lack of integrated psychological support within court processes. The study concludes that to protect women's matrimonial rights, there is an urgent need for clearer operational guidelines on emotional abuse, enhanced procedural directions for non-physical evidence, and strengthened court-linked psychological referral pathways.